Cinnamomum longepaniculatum essential oil-loaded weed suppression type liquid mulching film and preparation method thereof

A biodegradable liquid mulch film using oil camphor tree residues addresses environmental issues by incorporating essential oils into a stable carrier for sustained weed suppression and soil moisture retention, leveraging waste resources effectively.

CN120304225AInactive Publication Date: 2025-07-15YIBIN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510701634.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-28
Publication Date
2025-07-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing plastic plastic films are difficult to biodegrade, resulting in environmental pollution and waste of resources, and lack effective technology for de-oiling oil camphor leaf residue resource utilization.

Method used

Lignocellulose powder and biochar powder are prepared by deoiling leaf residue of oil camphor. Oil camphor essential oil is loaded and mixed with materials such as carboxymethyl cellulose, soluble starch and glycerol to form a liquid mulch film. Biochar and diatomaceous earth are used as carriers to encapsulate oil camphor essential oil.

Benefits of technology

It has achieved stable load and slow release of camphor essential oil, and has significant grass-repressing effects, avoiding resource waste and reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120304225A_ABST
    Figure CN120304225A_ABST
Patent Text Reader

Abstract

The invention discloses a cinnamomum longepaniculatum essential oil-loaded weed suppression type liquid mulching film and a preparation method thereof, and belongs to the technical field of liquid mulching films. The liquid mulching film is prepared from the deoiled cinnamomum longepaniculatum leaf residues obtained after essential oil extraction, the deoiled cinnamomum longepaniculatum leaf residues can be recycled, resource waste and environmental pollution are avoided, the deoiled cinnamomum longepaniculatum leaf residues contain natural active substances capable of inhibiting growth of weeds, the liquid mulching film can be endowed with the effect of inhibiting growth of weeds, and the utilization rate of the liquid mulching film is increased. The obtained liquid mulching film can be used for weeding. When the liquid mulching film is prepared, the cinnamomum longepaniculatum essential oil is encapsulated in the carrier formed by the charcoal powder and the diatomite, so that the stability of the cinnamomum longepaniculatum essential oil can be ensured, the carrier has excellent porosity and can load a large amount of cinnamomum longepaniculatum essential oil, and the weed suppression function of the obtained liquid mulching film is fully ensured; in addition, the cinnamomum longepaniculatum essential oil packaged in the carrier can be slowly released, so that the liquid mulching film can exert an excellent weed suppression effect within a relatively long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of liquid mulch film, and particularly relates to a weed-inhibiting liquid mulch film loaded with essential oil of Cinnamomum longepaniculatum and a preparation method thereof. Background Art

[0002] In agricultural production, the covering of mulch film plays an important role in promoting farmers to improve quality and increase production. The mulch film mainly inhibits weed growth, keeps warm and moist, and prevents the invasion of pests and diseases by covering the plastic film on the ground surface, thereby further improving the yield and quality of crops. Since plastic film is not easily degraded, and with the development of agriculture, the application scope is constantly expanding, the environmental problems caused by plastic film have begun to emerge. Traditional agricultural mulch films are basically non-biodegradable plastics, which not only remain in the soil for a long time and cannot be decomposed, but also bring great harm to the soil structure and ecological environment. In addition, due to the influence of various natural factors, plastic film is extremely easy to become small plastic particles during the decomposition process and flow into rivers with rainwater, causing serious pollution and damage to the water resource environment. These problems have received great attention all over the world today, and are also called "white pollution". In modern society, as people's requirements for natural resources become higher, the impact of non-degradable plastic film on the ecological environment has become more prominent. Therefore, finding or developing a green and biodegradable film is an important solution to solve this problem. Liquid mulch film is a new type of environmental protection film, which is mostly prepared from materials such as humic acid and polyvinyl alcohol, and has the advantages of environmental protection, biodegradability, improving soil fertility, promoting the growth of crops, and improving the yield and quality of crops, which has attracted people's attention in recent years.

[0003] As a natural woody spice with great economic value, the main producing area of Cinnamomum longepaniculatum is Yibin City, Sichuan Province, and the planting area has reached 650,000 mu. It has become one of the important economic pillars in Yibin area. Since the stems and leaves of Cinnamomum longepaniculatum are rich in essential oil components, they have great value in spices, perfumes, medicine, chemical industry, etc., and are in short supply in the international market, which has greatly promoted the development and growth of the Cinnamomum longepaniculatum planting industry. With the rapid expansion of the scale of the Cinnamomum longepaniculatum oil processing industry, due to the lack of effective resource utilization technology, a large amount of defatted leaf residue wood fiber of Cinnamomum longepaniculatum is disorderly stacked or improperly disposed, which not only causes serious environmental pollution problems, but also leads to the waste of precious biomass resources. This phenomenon has attracted extensive attention from domestic academia on the efficient utilization and green treatment technology of defatted leaf residue. Although this material has been limitedly applied to the preparation of edible mushroom culture medium, biomass energy production and polysaccharide extraction and other fields, the research on the high-value utilization of lignocellulose and the development of liquid mulch film is still blank. Summary of the Invention

[0004] In view of the above-mentioned prior art, the present invention provides a weed-inhibiting liquid mulch film loaded with essential oil of Cinnamomum longepaniculatum and a preparation method thereof, so as to develop a liquid mulch film with the characteristic of inhibiting weed growth.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is to provide a preparation method of a weed-inhibiting liquid mulch film loaded with essential oil of Cinnamomum longepaniculatum, comprising the following steps: S1: Prepare wood cellulose powder by using defatted leaf residue of Cinnamomum longepaniculatum; S2: Prepare biochar powder by using the wood cellulose powder; S3: Mix the carrier and the essential oil of Cinnamomum longepaniculatum according to the material-liquid ratio of 1 g: 2-5 mL, first stir magnetically, then shear, and then filter to collect the solid to obtain the oil-loaded carrier; the carrier is biochar powder and / or diatomite; S4: Dissolve sodium carboxymethylcellulose, soluble starch and glycerol in water, and then sequentially add glutaraldehyde solution and PVA solution to obtain a composite film-forming agent; S5: Add the wood cellulose powder and the oil-loaded carrier to the composite film-forming agent, and mix evenly to obtain the product.

[0006] On the basis of the above technical solution, the present invention can also be improved as follows.

[0007] Further, the preparation of the wood cellulose powder in S1 comprises the following steps: S11: Naturally air-dry the defatted leaf residue of Cinnamomum longepaniculatum after extracting the essential oil, and then crush it through a 0.1 mm sieve to obtain leaf residue powder; S12: Mix the leaf residue powder and a sodium hydroxide solution with a concentration of 2 wt% according to the material-liquid ratio of 1 g: 4-8 mL, keep it warm at 85-95 °C for 25-40 min, and then filter and wash it to neutrality to obtain alkali-treated leaf residue; S13: Mix the alkali-treated leaf residue and a laccase solution with a concentration of 1 U / mL according to the material-liquid ratio of 1 g: 1 mL, and carry out enzymatic hydrolysis fermentation at 35-45 °C for 18-30 h; then dry the enzymatically hydrolyzed material to obtain the product.

[0008] Further, the preparation of the biochar powder in S2 comprises the following steps: S21: Calcinate the wood cellulose powder in an inert atmosphere. The calcination process is to first heat it up to 100-120 °C at a heating rate of 10-15 °C / min and keep it warm for 10-20 min; then heat it up to 480-520 °C at a heating rate of 8-12 °C / min and keep it warm for pyrolysis for 90-150 min; then naturally cool it to room temperature; S22: Wash and crush the cooled powder to obtain the product.

[0009] Further, the carrier is composed of biochar powder and diatomite mixed according to the mass ratio of 1: 0.5-2.

[0010] Further, the carrier is formed by mixing biochar powder and diatomite in a mass ratio of 1:0.5.

[0011] Further, in S3, the carrier is mixed with camphor essential oil at a material-liquid ratio of 1 g:5 mL; the magnetic stirring speed is 400 - 500 r / min, and the stirring time is 1 h; the shear rate is 15,000 rpm, and the shear time is 2 min.

[0012] Further, in S4, the material-liquid ratio of sodium carboxymethylcellulose, soluble starch, glycerol and water is 1 - 2 g:1 - 2 g:0.5 - 1.5 g:85 - 95 mL; the concentration of glutaraldehyde solution is 0.2 wt%, the concentration of PVA solution is 2 wt%, and the volume ratio of glutaraldehyde solution, PVA solution and water is 1:1:9.

[0013] Further, in S5, the volume ratio of lignocellulose powder, oil-loaded carrier and composite film-forming agent is 1 - 6:4 - 9:40.

[0014] Further, the volume ratio of lignocellulose powder, oil-loaded carrier and composite film-forming agent is 2:8:40.

[0015] The present invention also discloses a weed-inhibiting liquid mulch film loaded with camphor essential oil prepared by the above preparation method.

[0016] The beneficial effects of the present invention are as follows: 1. The present invention uses the defatted leaf residue of camphor after extracting essential oil as a raw material to prepare a liquid mulch film, which can not only recycle the defatted leaf residue of camphor, avoid waste of resources and environmental pollution, but also, the defatted leaf residue of camphor contains natural active substances that inhibit the growth of weeds, which can endow the liquid film with the effect of inhibiting the growth of weeds, so that the obtained liquid mulch film can be used for weed control.

[0017] 2. When preparing the liquid mulch film in the present invention, the camphor essential oil is encapsulated in the carrier formed by biochar powder and diatomite, which can not only ensure the stability of the camphor essential oil, but also the carrier has excellent porosity and can load a large amount of camphor essential oil, fully guaranteeing the weed-inhibiting function of the obtained liquid mulch film; in addition, the camphor essential oil encapsulated in the carrier can be slowly released, so that the liquid mulch film can exert excellent weed-inhibiting effects for a long time. Description of the Drawings

[0018] Figure 1 It is a test result graph of the loading rate of camphor essential oil in the carrier; Figure 2 It is a test result graph of the slow-release performance of the carrier for camphor essential oil; Figure 3 It is a morphology graph of the lignocellulose-CMC-based liquid mulch film; Figure 4 It is a morphological diagram of the lignocellulose-CMC-PVA-based liquid mulch film; Figure 5 It is a test result diagram of the swelling performance of the lignocellulose-CMC-based liquid mulch film; Figure 6 It is a test result diagram of the swelling performance of the lignocellulose-CMC-PVA-based liquid mulch film; Figure 7 It is a test result diagram of the solubility of the lignocellulose-CMC-based liquid mulch film; Figure 8 It is a test result diagram of the solubility of the lignocellulose-CMC-PVA-based liquid mulch film; Figure 9 It is a test result diagram of the film-forming performance of the liquid mulch film after adding the compound carrier; Figure 10 It is a test result diagram of the swelling performance of the liquid mulch film after adding the compound carrier; Figure 11 It is a test result diagram of the dissolution performance of the liquid mulch film after adding the compound carrier; Figure 12 It is a test result diagram of the swelling rate and solubility of the liquid mulch film after adding the carrier loaded with essential oil of Cinnamomum longepaniculatum; Figure 13 It is a test result diagram of the water retention performance of the liquid mulch film after adding the carrier loaded with essential oil of Cinnamomum longepaniculatum; Figure 14 It is the water retention curve of the liquid mulch film after adding the carrier loaded with essential oil of Cinnamomum longepaniculatum; Figure 15 It is a test result diagram of the viscosity of the liquid mulch film after adding the carrier loaded with essential oil of Cinnamomum longepaniculatum; Figure 16 It is the weed suppression effect diagram of the PMC liquid mulch film. Specific implementation manners

[0019] The reagents used in the embodiments of the present invention are shown in the following table: Reagent Name Purity Manufacturer Essential Oil of Cinnamomum longepaniculatum >55.00% Yibin Shiping Spice Co., Ltd. Sodium Hydroxide >99.90% Junzheng Group Sodium Carboxymethyl Cellulose 99.00% Henan Qinuo Food Ingredients Co., Ltd. Laccase 50.00% Hubei Kemadi Chemical Co., Ltd. Polyvinyl Alcohol >93.50% Sichuan Chuanwei Co., Ltd. Soluble Starch 99.00% Shanxi Jinyang Pharmaceutical Excipients Co., Ltd. Glycerol 99.50% Shandong Yonglida New Material Technology Co., Ltd. Glutaraldehyde 99.00% Jinan Tengbo Chemical Co., Ltd. The specific implementation manners of the present invention will be described in detail below in conjunction with the embodiments.

[0020] Example 1: Preparation of lignocellulose by treating defatted leaf residue wood fiber of Cinnamomum longepaniculatum with an enzyme-alkali dual treatment method The defatted leaf residue of Cinnamomum longepaniculatum after extracting essential oil is naturally air-dried and then pulverized. Then, large particles and impurities are sieved out through a 0.1-mm sieve to obtain leaf residue powder. The pulverized and sieved leaf residue powder is fully mixed with a sodium hydroxide solution with a concentration of 2 wt% at a solid-liquid ratio of 1 g:5 mL. Subsequently, it is treated in a 90°C water bath for 30 min. After the water bath treatment, the mixture is poured onto a 100-mesh high-density wire mesh and washed repeatedly with tap water until the water flow is clear and the pH value is measured to be neutral to ensure that the sodium hydroxide on the surface of the leaf residue is completely removed. Finally, the washed leaf residue powder is mixed with a laccase solution of 1 U / mL at a solid-liquid ratio of 1 g:1 mL, sealed, and enzymatically hydrolyzed and fermented at 40°C for 24 h. After the enzymatic hydrolysis is completed, the treated material is dried to obtain wood cellulose powder.

[0021] Example 2: Preparation of wood fiber biochar from defatted leaf residue of Cinnamomum longepaniculatum The wood cellulose powder prepared in Example 1 is weighed by a precision balance and transferred to a horizontal tube cracking furnace. The nitrogen purge system (purity ≥99.999%) is started, and nitrogen is continuously introduced at a flow rate of 150 mL / min for 15 min. The heating program is set for two-stage temperature control: first, it is heated to 110°C at a heating rate of 12°C / min and kept at a constant temperature for 15 min to complete the pre-dehydration of the raw material. Subsequently, the heating rate is switched to 10°C / min and heated to the final temperature of 500°C, and the constant-temperature cracking stage is maintained for 120 min. During this period, the temperature uniformity of the furnace body is monitored by an infrared thermal imager (deviation ≤±3°C); the whole cracking process is kept under positive nitrogen pressure protection (0.2~0.3 MPa). After the cracking is completed, the product is naturally cooled to room temperature, and then the surface ash is removed by an ultrasonic-assisted water washing-centrifugation cycle process (3 times × 10 min), and then it is co-treated by a planetary ball mill (rotation speed 400 rpm × 4 h) and a jet mill (classification wheel rotation speed 6000 rpm) to obtain micro-nano biochar powder.

[0022] Example 3: Preparation of biochar and diatomite loaded with essential oil of Cinnamomum longepaniculatum The solid-oil ratios (g:mL) of biochar (prepared in Example 2) or diatomite to the essential oil of Cinnamomum longepaniculatum are all set to 1:2, 1:3, 1:4, and 1:5. Among them, the single biochar treatment groups are designated as A1, A2, A3, and A4, and the single diatomite treatment groups are designated as B1, B2, B3, and B4. At the same time, the biochar and diatomite are compounded at a mass ratio of 1:0.5 to obtain a composite carrier, and then the composite carrier is mixed with the essential oil of Cinnamomum longepaniculatum at solid-oil ratios of 1:2, 1:3, 1:4, and 1:5. This treatment group is designated as C1, C2, C3, and C4.

[0023] Add biochar, diatomite or compound carrier to the essential oil of Cinnamomum longepaniculatum according to the above ratios and stir in a magnetic stirrer (400 - 500 r / min) for 1 hour, then shear at a speed of 15,000 rpm in a high-speed shearer for 2 min, and then filter. The filtrate is used for analyzing the loading amount test of the essential oil of Cinnamomum longepaniculatum, and the solid part is used for evaluating the sustained-release performance of the essential oil of Cinnamomum longepaniculatum. The method for testing the loading amount of the essential oil of Cinnamomum longepaniculatum is as follows: Take the filtered solution after impregnating the corresponding carrier with the essential oil of Cinnamomum longepaniculatum, measure the transmittance at 480 nm with a spectrophotometer, and calculate the loading rate (LE) of the essential oil on different carriers according to the following formula: LE=(C0 - C1) / C0 * 100% In the formula, C0 is the transmittance of the essential oil solution before adding the carrier; C1 is the transmittance of the essential oil solution after adding the carrier. The test results of the carrier essential oil loading rate are as Figure 1 shown. It can be seen from Figure 1 that after mixing biochar alone with the essential oil of Cinnamomum longepaniculatum in different ratios, with the increase of the material-oil ratio, the loading efficiency shows a trend of first increasing and then decreasing. The loading efficiency reaches the maximum of 48.6% at A3 and the minimum of 26.8% at A1. Similarly, after mixing diatomite with the essential oil of Cinnamomum longepaniculatum in different ratios, with the increase of the material-oil ratio, the loading efficiency also shows a trend of first increasing and then decreasing. The loading efficiency reaches the maximum value of 31.3% at B3 and the minimum of 19.7% at B1. After compounding biochar and diatomite and mixing them with the essential oil of Cinnamomum longepaniculatum in different ratios, the loading efficiency gradually increases with the increase of the material-oil ratio and reaches the maximum value of 44.6% at C4.

[0024] The method for evaluating the sustained-release performance of the carrier on the essential oil of Cinnamomum longepaniculatum is as follows: Place the solid part after filtering the impregnated essential oil of Cinnamomum longepaniculatum on an evaporating dish, and count the weight reduction at specific time points under a fixed wind speed, and calculate the release amount of each carrier at each time point. Take time as the abscissa and release amount as the ordinate to plot the essential oil release curves of different carriers. By observing the trend and changes of the curves, analyze the sustained-release performance of different carriers. The test results of the sustained-release performance of the carrier on the essential oil of Cinnamomum longepaniculatum are as Figure 2 shown. It can be seen from Figure 2 that in the single biochar carrier treatment group, with the increase of time, the essential oil release amount gradually decreases in each treatment. Among them, the sustained-release curve of A3 is flatter and the sustained-release effect is the best. In the single diatomite treatment group, with the increase of time, the essential oil release amount also gradually decreases in each treatment, and the best sustained-release effect is B3. In the group of compounded biochar and diatomite, with the increase of time, the essential oil release amount also gradually decreases in each treatment, and the best sustained-release effect is C4.

[0025] Example 4: Screening the basic liquid mulch film with essential oil carrier added 1. Preparation of lignocellulose-CMC-based liquid mulch film Mix the lignocellulose prepared in Example 1 with a sodium carboxymethylcellulose solution (CMC solution) with a concentration of 1.5 wt% at a volume ratio of 1:4 and stir. Set the stirring time to 50 minutes to ensure sufficient contact and uniform mixing of the lignocellulose and the solution. After uniform stirring, it is the lignocellulose-CMC-based liquid mulch film, and set the code for this group as CM. Then replace 20%, 40%, and 60% of the volume of lignocellulose in CM with diatomaceous earth (the prepared mulch film codes are CM1, CM2, and CM3) or the same percentage of biochar (the prepared mulch film codes are CM4, CM5, and CM6) respectively to determine the optimal carrier addition amount, with CK1 without diatomaceous earth and biochar as the control. Pour the above mixed solution into a mold of 25 cm × 10 cm × 5 cm and conduct a drying treatment at a temperature of 45 °C. The prepared mulch film is used for performance testing. The morphology of the prepared mulch film is as Figure 3 shown. As can be seen from Figure 3 , based on the lignocellulose-CMC liquid mulch film as the basic mulch film, after adding diatomaceous earth or biochar carriers that replace 20%, 40%, and 60% of the volume of lignocellulose, each treatment can form a film under the test conditions. Among them, the best film-forming effect is CM1 and CM4. However, after the prepared film is dried, compared with the control CK1, with the increase of the addition ratio of diatomaceous earth or biochar, the ductility of the formed film becomes worse and worse. When the proportion of diatomaceous earth or biochar is 60%, the formed film is extremely easy to break.

[0026] 2. Preparation of lignocellulose-CMC-PVA-based liquid mulch film 1.5 g of sodium carboxymethyl cellulose, 1.2 g of soluble starch, and 1 g of glycerol were added to 90 mL of distilled water. The mixture was stirred with an electric stirrer in a 90 °C water bath until completely dissolved into a transparent liquid. Then, 10 mL of a 0.2 wt% glutaraldehyde solution was added. After stirring at 800 r / min in a 90 °C water bath for 30 minutes, an equal volume of a 2 wt% PVA solution was added, and stirring continued at 800 r / min in a 90 °C water bath for 150 minutes to obtain a composite film-forming agent. The lignocellulose prepared in Example 1 was mixed with the composite film-forming agent at a volume ratio of 1:4 and stirred. The stirring time was set to 50 minutes to obtain a lignocellulose-CMC-PVA liquid mulch film, designated as PM. Then, 20%, 40%, and 60% of the volume of lignocellulose in PM were respectively replaced with diatomaceous earth (the prepared mulch films were designated as PM2, PM3, and PM4) or the same percentage of biochar (the prepared mulch films were designated as PM5, PM6, and PM7) to determine the optimal carrier addition amount, with CK2 without diatomaceous earth and biochar as the control. The above-mentioned mixed solution was poured into a mold of 25 cm × 10 cm × 5 cm and dried at a temperature of 45 °C. The prepared mulch film was used for performance testing. The morphology of the prepared mulch film is as Figure 4 shown. As can be seen from Figure 4 , after adding diatomaceous earth or biochar carriers to replace lignocellulose in the lignocellulose-CMC-PVA-based liquid mulch film, films could be formed in each treatment. However, compared with the control CK2, with the increase in the addition ratio of the carrier diatomaceous earth or biochar in each treatment, the ductility of the formed film gradually became worse, and the breaking ratio of the film gradually increased. When the addition ratio of diatomaceous earth or biochar was 60%, the formed film was extremely easy to break. Among the treatment groups, PM1 with diatomaceous earth added and PM4 with biochar added had the best film-forming effect.

[0027] The swelling degree of the above-prepared mulch film was tested, and the test method was as follows: The prepared and dried liquid mulch film was cut into 2 cm × 2 cm squares, and the mass was accurately weighed with an electronic balance and recorded as M0. Then, these dried film samples were immersed in a cup containing 20 mL of deionized water and left at room temperature for 40 minutes to fully absorb water and reach swelling equilibrium. Then, the swollen samples were filtered through a 100-mesh nylon mesh and suspended for 10 minutes until there was no free water on the surface, and recorded as M1. The swelling rate was calculated by the following formula: SR = M0 / M1 * 100% where SR is the swelling rate of the mulch film (%); M0 is the mass of the mulch film before swelling (g); M1 is the mass of the mulch film after swelling (g).

[0028] The test results of the swelling performance of the lignocellulose-CMC-based liquid mulch film are as Figure 5 shown. As can be seen from Figure 5It can be seen that the swelling rate of the lignocellulose-CMC-based liquid mulch film with essential oil carriers changes significantly with the increase in the proportion of the carrier replacing the camphor leaf residue lignocellulose. Among them, in the treatment group with a single diatomite carrier, as the amount of diatomite added increases, the swelling rate of the liquid mulch film gradually decreases. However, among all treatment groups, the swelling rate of CM1 is significantly higher than that of CM2 and CM3. Compared with CK1, the swelling rate of CM1 increases by 186%, while the swelling rates of CM2 and CM3 decrease by 22.2% and 29.1% respectively. In the treatment group with a single biochar carrier, as the amount of biochar added increases, the swelling rate of the liquid mulch film also gradually decreases. The swelling rate of CM4 is significantly greater than that of CM5 and CM6. Among them, the swelling rate of CM4 increases by 130.4% compared with CK1, while the swelling rates of CM5 and CM6 decrease by 11.3% and 37.4% respectively compared with CK1. Among them, CM1 with diatomite added is significantly greater than CM4 with biochar added.

[0029] The test results of the swelling performance of the lignocellulose-CMC-PVA-based liquid mulch film are as Figure 6 shown. It can be seen from Figure 6 that the swelling rates of the lignocellulose-CMC-PVA-based liquid mulch films with different carriers have changed greatly. In each treatment group, as the amounts of diatomite and biochar added increase, the swelling rates of the prepared liquid mulch films gradually decrease. However, at the same addition ratio, the swelling properties of the liquid mulch films in the treatment groups with biochar added are significantly higher than those in the treatment groups with diatomite added. Further analysis shows that in the treatment group with diatomite added, the swelling rate of PM2 increases by 163% compared with CK2; PM3 and PM4 decrease by 13.2% and 58.6% respectively. Compared with CK2, the swelling rates of PM5 and PM6 with biochar added increase by 183.5% and 148.6% respectively. PM7 decreases by 21.4%. Among the two treatment groups, the best swelling rates are for PM2 and PM5, but the swelling rate of PM5 with biochar added is significantly higher than that of PM2 with diatomite added.

[0030] The solubility of the above-prepared mulch films was tested, and the test method is as follows: The liquid mulch film sample was cut into square test pieces of 2 cm × 2 cm, and the initial mass was measured as M0 after continuous drying in a 45°C vacuum drying oven for 10 hours. To investigate the water response characteristics of the material, the pretreated test pieces were completely immersed in deionized water for 24 hours. After the surface free water was wiped clean with filter paper, they were placed in a drying environment at the same temperature for dehydration treatment for 10 hours, and the mass change value was recorded by a precision electronic balance and denoted as M1. The dissolution rate was calculated by the following formula: S = (M0 - M1) / M0 * 100% Wherein, S is the dissolution rate of the plastic film (%); M0 is the initial weight of the plastic film (g); M1 is the weight of the plastic film after dissolution (g).

[0031] The solubility test results of the lignocellulose-CMC-based liquid plastic film are as Figure 7 shown. From left to right in the figure are CK1, CM6, CM5, CM4, CM3, CM2, and CM1. It can be seen from Figure 7 this that all treatments of the lignocellulose-CMC-based liquid plastic film with the addition of carrier diatomite or biochar are completely dissolved in water, indicating that this plastic film may dissolve due to the action of water during practical use and cannot form a protective layer. Therefore, the performance of this basic plastic film should be further optimized for subsequent applications.

[0032] The solubility test results of the lignocellulose-CMC-PVA-based liquid plastic film are as Figure 8 shown. From left to right in the figure are PM7, PM6, PM5, PM4, PM3, PM2, and CK2. It can be seen from Figure 8 this that after adding carrier diatomite or biochar, the lignocellulose-CMC-PVA liquid plastic films of each treatment are not completely dissolved in water, all have good water resistance, and their hydrolysis property is significantly reduced compared with the lignocellulose-CMC-based liquid plastic film, and the anti-solubility is better.

[0033] After comprehensively evaluating the film-forming properties and performance of the above two basic liquid plastic films, it is found that when the proportion of the carrier replacing lignocellulose is 20%, the film-forming property and the performance of the film are better; among the basic plastic films, according to the solubility, it is found that the lignocellulose-CMC-PVA-based liquid plastic film has the best anti-hydrolysis ability. Therefore, this treatment group is selected for subsequent experiments.

[0034] Example 5: Preparation of a liquid plastic film with a compound carrier added According to the test results in Example 4, after screening out the optimal addition amount of the carrier, in order to improve the essential oil loading rate, the influence of different ratios of biochar and diatomite compounded on the performance of the plastic film is further screened. Among them, the compound ratio (mass ratio) of biochar and diatomite is set to 1:0.5, 1:1, 1:1.5, and 1:2. After adding the above-mentioned different ratios of compounded biochar and diatomite to the lignocellulose-CMC-PVA-based liquid plastic film (the addition amount is to replace 20% of the volume of lignocellulose), the treatment codes of each treatment are CP1, CP2, CP3, and CP4 in turn. After adding different ratios of biochar and diatomite to the lignocellulose-CMC-based liquid plastic film (the addition amount is to replace 20% of the volume of lignocellulose), the treatment codes of each treatment are CP5, CP6, CP7, and CP8 in turn. After preparing different liquid plastic films, relevant performance analysis is carried out.

[0035] After adding the compound carrier, the film-forming performance test results of the liquid plastic film are asFigure 9 As shown. From Figure 9 It can be seen that after adding diatomite and biochar carriers with different compounding ratios to the lignocellulose-CMC-based liquid mulch film and the lignocellulose-CMC-PVA-based liquid mulch film, each treatment can form a film. However, through mutual comparison of each group, it is found that the film-forming effects of treatments CP1 and CP5 are the best after film formation, that is, the best compounding ratio of biochar and diatomite is 1:0.5.

[0036] After adding the compound carrier, the test results of the swelling performance of the liquid mulch film are as Figure 10 shown. From Figure 10 It can be seen that in the treatment group of the liquid mulch film based on lignocellulose-CMC-PVA, with the increase in the proportion of diatomite in the compound carrier, the swelling rate of the prepared liquid mulch film gradually decreases, and the swelling property of treatment CP1 (compounding ratio of 1:0.5) is the best. For the treatment group of the liquid mulch film based on lignocellulose-CMC, with the increase in the proportion of diatomite in the compound carrier, the swelling property of each treatment liquid mulch film first increases and then decreases, and the swelling property of treatment CP8 (compounding ratio of 1:2) is the best, and the swelling property of this series of liquid mulch films is significantly higher than that of the treatment group of the lignocellulose-CMC-PVA-based liquid mulch film.

[0037] After adding the compound carrier, the test results of the dissolution performance of the liquid mulch film are as Figure 11 shown. From left to right in the figure are CP8, CP7, CP6, CP5, CP4, CP3, CP2, CP1. From Figure 11 It can be seen that after adding the compound carriers of diatomite and biochar, the lignocellulose-CMC-PVA-based liquid mulch films all have good water resistance, and the best one is CP1 (1:0.5), while most of the films of the lignocellulose-CMC-based liquid mulch film dissolve after adding the compound carrier.

[0038] After comprehensively evaluating the film-forming property and related properties of the above two liquid mulch films after adding the compound carrier, it is found that when the compounding ratio of biochar and diatomite is 1:2, the film-forming property and film properties of the liquid mulch film based on lignocellulose-CMC are better. When the ratio of biochar to diatomite carrier is 1:0.5, the film-forming property and film properties of the lignocellulose-CMC-PVA liquid mulch film are better. According to the solubility, it is found that the hydrolysis resistance of the lignocellulose-CMC-PVA-based liquid mulch film in this treatment group is the best, so this treatment group is selected for subsequent experiments.

[0039] Example 6: Preparation of a liquid mulch film with a carrier loaded with essential oil of Cinnamomum longepaniculatum Based on the test results of the above embodiments, using the screened optimal basic liquid mulch film (lignocellulose-CMC-PVA liquid mulch film) and the screened single biochar, diatomite, and the carrier prepared by compounding the two as the basis, after loading the carrier with cinnamomum longepaniculatum oil (the preparation method is shown in Example 3), a liquid mulch film was prepared (the preparation method is shown in Example 4). Among them, the treatment with a single biochar carrier is defined as PMA, the treatment with a single diatomite carrier is defined as PMB, and the treatment with a biochar and diatomite compounded at a ratio of 1:0.5 is defined as PMC.

[0040] The swelling rate and solubility test results of the prepared liquid mulch films are respectively as Figure 12 shown. It can be seen from Figure 12 that the PMB liquid mulch film has the highest swelling rate, reaching 768%, followed by the PMC liquid mulch film, and the PMA liquid mulch film has the worst swelling property; while the PMA and PMC liquid mulch films have the highest dissolution rate, followed by PMB, and only 10% is dissolved.

[0041] The water retention property of the liquid mulch film can inhibit the evaporation of soil moisture, keep the soil moist for a long time, and improve the soil structure. The water retention properties of the PMA, PMB, and PMC liquid mulch films were tested, and the test method is as follows: Add 50 g of dried soil to each of 8 transparent petri dishes of the same size, and gradually add deionized water until water seeps out; two of the petri dishes are not sprayed with any liquid mulch film as a control, and the other 6 petri dishes are divided into three groups, and 50 mL of 3 different liquid mulch films are evenly sprayed respectively. Leave it still at room temperature for one week, and observe the water evaporation in the petri dishes. The results are as Figure 13 shown. And during the standing period, the total mass of the petri dish and the soil is measured at the same time every day, and the water evaporation is compared by the mass difference. The water retention property (G) is calculated by the following formula: G = (G0 - G1) / G0 In the formula, G is the water retention property; G0 is the total mass of the petri dish and the soil at the beginning (g); G1 is the total mass of the petri dish and the soil after the same time interval (g). Taking the time interval as the abscissa and the water retention property as the ordinate, a water retention curve is constructed. The results are as Figure 14 shown. It can be seen from Figure 13 and Figure 14 that all three liquid mulch films have a certain water retention property; and the best water retention property is PMC, followed by PMB, and finally PMA.

[0042] The viscosity of the liquid mulch film determines the adhesion ability and fluidity of the liquid mulch film on the soil surface, and has a great influence on the related properties of the mulch film. The viscosities (Eta) of the PMA, PMB, and PMC liquid mulch films were tested, and the test method is as follows: Centrifuge the three kinds of liquid mulches to ensure that there are no air bubbles or precipitates in the samples. Then, select the RV rotor and use a rotational viscometer for measurement. Set the test temperature at 25 °C, select a rotational speed of 100 rpm, press the start button, and the instrument will automatically measure the viscosity. Export the measured file, and clean the rotor and measuring cup after the test. Process the data at the 30 s measurement time to evaluate the film-forming performance of the liquid mulches.

[0043] The test results of the viscosity of the liquid mulches are as Figure 15 shown. It can be seen from Figure 15 that there are certain differences in the viscosities of the three kinds of liquid mulches prepared after the carrier is loaded with essential oils. Among them, the viscosity of PMC is the highest at 414.1 (mPa·s), followed by PMB and PMA in turn. Considering all indicators, the PMC treatment group has the best performance.

[0044] Test the performance of the PMC liquid mulch in inhibiting weeds. The test method is as follows: Add the soilless cultivation substrate for blueberries sieved through a 2 mm sieve into the planting pots, and then plant blueberries in the conventional soilless cultivation method. Spray the PMC liquid mulch (experimental group) at a spraying rate of 1.9 L / m 2 , and set a control group without spraying the PMC liquid mulch for conventional management. The results are as Figure 16 shown. The left side in the figure is the control group, and the right side is the experimental group. It can be seen from Figure 16 that the PMC liquid mulch has a relatively significant inhibitory effect on weeds and can be used in subsequent production practices.

[0045] Although the specific implementation modes of the present invention have been described in detail in combination with the embodiments, it should not be construed as a limitation on the protection scope of this patent. Within the scope described in the claims, various modifications and deformations that can be made by those skilled in the art without creative efforts still fall within the protection scope of this patent.

Claims

1. A preparation method of a weed-inhibiting liquid mulch film loaded with essential oil of Cinnamomum longepaniculatum, characterized in that, It includes the following steps: S1: Prepare lignocellulose powder from defatted Cinnamomum longepaniculatum leaves residue; S2: Prepare biochar powder from lignocellulose powder; S3: Mix the carrier and Cinnamomum longepaniculatum essential oil at a liquid-to-solid ratio of 1 g: 2 - 5 mL, first stir magnetically, then shear, and then filter to collect the solid to obtain the oil-loaded carrier; the carrier is biochar powder and / or diatomite; S4: Dissolve sodium carboxymethylcellulose, soluble starch, and glycerol in water, and then sequentially add glutaraldehyde solution and PVA solution to obtain a composite film-forming agent; S5: Add the lignocellulose powder and the oil-loaded carrier to the composite film-forming agent and mix evenly to obtain the product.

2. The preparation method according to claim 1, characterized in that, The preparation of the lignocellulose powder in S1 includes the following steps: S11: Naturally air-dry the defatted Cinnamomum longepaniculatum leaves residue after extracting essential oil, then crush it through a 0.1 mm sieve to obtain leaf residue powder; S12: Mix the leaf residue powder with a 2 wt% sodium hydroxide solution at a liquid-to-solid ratio of 1 g: 4 - 8 mL, keep it warm at 85 - 95 °C for 25 - 40 min, then filter and wash until neutral to obtain alkali-treated leaf residue; S13: Mix the alkali-treated leaf residue with a 1 U / mL laccase solution at a liquid-to-solid ratio of 1 g: 1 mL, enzymatically hydrolyze and ferment at 35 - 45 °C for 18 - 30 h; then dry the enzymatically hydrolyzed material to obtain the product.

3. The preparation method according to claim 1, characterized in that, The preparation of the biochar powder in S2 includes the following steps: S21: Calcinate the lignocellulose powder in an inert atmosphere. The calcination process is to first heat it at a heating rate of 10 - 15 °C / min to 100 - 120 °C and keep it warm for 10 - 20 min; then heat it at a heating rate of 8 - 12 °C / min to 480 - 520 °C and keep it warm and pyrolyze for 90 - 150 min; then naturally cool it to room temperature; S22: Wash and crush the cooled product to obtain the product.

4. The preparation method according to claim 1, characterized in that: The carrier is composed of biochar powder and diatomite mixed in a mass ratio of 1: 0.5 - 2.

5. The preparation method according to claim 4, characterized in that: The carrier is composed of biochar powder and diatomite mixed in a mass ratio of 1: 0.

5.

6. The preparation method according to claim 5, wherein: In S3, the carrier and Cinnamomum longepaniculatum essential oil are mixed at a liquid-to-solid ratio of 1 g: 5 mL; the magnetic stirring speed is 400 - 500 r / min, and the stirring time is 1 h; the shear rate is 15000 rpm, and the shear time is 2 min.

7. The preparation method according to claim 1, characterized in that: In S4, the liquid-to-solid ratio of sodium carboxymethylcellulose, soluble starch, glycerol to water is 1 - 2 g: 1 - 2 g: 0.5 - 1.5 g: 85 - 95 mL; the concentration of the glutaraldehyde solution is 0.2 wt%, the concentration of the PVA solution is 2 wt%, and the volume ratio of the glutaraldehyde solution and the PVA solution to water is 1: 1:

9.

8. The preparation method according to claim 1, characterized in that: In S5, the volume ratio of the lignocellulose powder, the oil-loaded carrier to the composite film-forming agent is 1 - 6: 4 - 9:

40.

9. The preparation method according to claim 8, characterized in that: The volume ratio of the lignocellulose powder, the oil-loaded carrier to the composite film-forming agent is 2: 8:

40.

10. The herbicidal liquid mulch film loaded with Cinnamomum longepaniculatum essential oil prepared by the preparation method according to any one of claims 1 - 9.